Whistleblowing Behavior Model and Social Influence : A Systematic Literature Review - Erwandy Erwandy; Arissetyanto Nugroho; Harnovinsah Harnovinsah; Darmansyah Darmansyah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Whistleblowing is a vital mechanism for exposing unethical practices and ensuring accountability in organizations. This systematic literature review explores the interplay between the Theory of Planned Behaviour (TPB) and social influence factors—conformity, compliance, and obedience—in shaping whistleblowing behaviour. The review examines empirical and theoretical studies from 2004 to 2024 to identify how TPB constructs (attitudes, subjective norms, and perceived behavioural control) integrate with social influence dynamics to influence the intention and action of whistleblowing. The findings highlight that attitudes toward whistleblowing, shaped by personal ethics and organizational culture, significantly influence individuals’ willingness to report misconduct. Subjective norms, reflecting the perceived social pressure to act or remain silent, often intersect with conformity and compliance, either encouraging or deterring whistleblowing. Perceived behavioural control, influenced by organizational support structures and fear of retaliation, determines the feasibility of acting. The role of obedience to authority emerges as a double-edged sword, where supportive leadership fosters whistleblowing while hierarchical pressures discourage it. Furthermore, the review underscores the importance of ethical climates and whistle-blower protection mechanisms in mitigating the negative impact of social pressures. It also identifies gaps in existing research, including the limited exploration of whistleblowing in diverse cultural contexts and the lack of longitudinal studies examining long-term impacts. This study contributes to the literature by providing an integrated framework that combines TPB and social influence theories to understand whistleblowing behaviour. It offers practical insights for policymakers and organizational leaders to design interventions that encourage ethical reporting and protect whistle blowers.